PEMBELAJARAN DARING PADA MASA COVID 19: STUDI KASUS PADA SEKOLAH MENENGAH KEJURUAN - Moh. Chairil Asmawan; Brian Arianto (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2022)
This study aims to determine the implementation process and the obstacles experienced during online learning. This type of research uses qualitative research with a case study design. Data collection techniques used are observation, interviews and documentation. The results show that 1) the process of implementing online learning has been going well using several media, namely Google Classroom, Google Form, Whatsapp, Zoom and several websites. The process begins with scheduling at the beginning of the semester, implementing the learning process and ending with an evaluation; 2) Constraints that occur during online learning at SMKN 3 Sukoharjo come from internal and external factors. Internal factors are laziness and addiction to playing games. While external factors are limited signal and internet quota used to access learning, lack of teacher knowledge or mastery of IT related to the media used during online learning; 3) The solution applied to internal factors for students is that the teacher always provides motivation at the beginning of the learning process by giving points each student can answer questions from the teacher, the solution that can be given to teachers is to provide training and coaching for teachers related to online learning. Then for external factors, namely providing free quota assistance to students, delivering material through media that does not drain internet quota too much, scheduling that has been neatly arranged so that students can know when to find a place to get a strong signal during the learning process.